2005
DOI: 10.1111/j.1365-2265.2005.02256.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of adrenal androgen excess in patients with the polycystic ovary syndrome (PCOS)

Abstract: The prevalence of DHEAS excess is approximately 20% among White and 30% among Black PCOS patients, when using age- and race-adjusted normative values. This study also indicates that the age-associated decline in DHEAS levels is observable and similar in both control and PCOS women, regardless of race. While BMI and fasting insulin had little impact on circulating DHEAS levels in healthy women, among White PCOS patients these parameters were negatively associated with circulating DHEAS levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
116
1
11

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(140 citation statements)
references
References 33 publications
12
116
1
11
Order By: Relevance
“…In contrast to these findings, two studies found decreased DHEAS levels in Black and Mexican American vs. white women with PCOS (23;24). Using race specific cut offs, black women with PCOS had increased prevalence of high DHEAS levels (23) suggesting that adrenal activity may differ between some ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these findings, two studies found decreased DHEAS levels in Black and Mexican American vs. white women with PCOS (23;24). Using race specific cut offs, black women with PCOS had increased prevalence of high DHEAS levels (23) suggesting that adrenal activity may differ between some ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoandrogenism is a consistent finding in male patients with MS [84]. In females, androgen metabolism is also altered, especially in those affected by polycystic ovary syndrome [85]. In all cases, the levels of dehydroepiandrosterone tend to be low [86] because of altered adrenal function, as in advanced age.…”
Section: Sex Hormonesmentioning
confidence: 65%
“…Certain studies have revealed higher levels of testosterone in the follicular fluid of patients with PCOS (37,38). Hyperandrogenism in PCOS may proceed via dysregulated paracrine/endocrine control of androgen synthesis (37), or result from adrenal androgen excess (39,40). Intraovarian androgens have been found to promote GC proliferation and inhibit GC apoptosis in PCOS patients, particularly in small follicles whose GCs are rich in androgen receptors (35,36), indicating that androgens may have a crucial effect on GC development, and intraovarian androgen may play an important role in the pathogenesis of PCOS via regulating early follicle growth.…”
Section: Discussionmentioning
confidence: 99%